2016
DOI: 10.1088/0953-8984/28/36/365302
|View full text |Cite
|
Sign up to set email alerts
|

Validity criteria for Fermi’s golden rule scattering rates applied to metallic nanowires

Abstract: Fermi's golden rule underpins the investigation of mobile carriers propagating through various solids, being a standard tool to calculate their scattering rates. As such, it provides a perturbative estimate under the implicit assumption that the effect of the interaction Hamiltonian which causes the scattering events is sufficiently small. To check the validity of this assumption, we present a general framework to derive simple validity criteria in order to assess whether the scattering rates can be trusted fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The impact is more pro-nounced in case of an isotropic collision time as compared to an isotropic mean free path and this can be understood by having a closer look at the conductivity expressions in Eqs. (11), (20) and (26). In case of an isotropic collision time, both the effective mass along the transport direction and the parameter for grain boundary scattering are renormalized w.r.t.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact is more pro-nounced in case of an isotropic collision time as compared to an isotropic mean free path and this can be understood by having a closer look at the conductivity expressions in Eqs. (11), (20) and (26). In case of an isotropic collision time, both the effective mass along the transport direction and the parameter for grain boundary scattering are renormalized w.r.t.…”
Section: Discussionmentioning
confidence: 99%
“…While it is hard to guarantee film continuity for the samples at very low thicknesses, several limitations and approximations underlying the Mayadas-Shatzkes model and its extension (including the consideration of a three-dimensional wave vector, the phenomenological treatment of boundary surface scattering and the perturbative treatment of grain boundary scattering) could also be (partially) responsible for a systematic underestimation (already remarked by Choi et al [22]). A recent validity analysis showed that this is certainly the case for a perturbative treatment of boundary surface scattering due to surface roughness and grain boundary scattering for extremely narrow nanowires [11]. Additionally, the consideration of a single (diagonal) effective mass (tensor) could be too approximate for complicated Fermi surfaces such as for Ru.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One should of course keep in mind that this is a perturbative approach, which is valid only for smallenough width variations. 62 The resistivity as a function of the roughness correlation length Λ AER is shown in Fig. 6(a) for the three 10-nm-wide GNRs of Fig.…”
Section: Transportmentioning
confidence: 99%